Enamel Matrix Derivatives as an Adjunct to Alveolar Ridge Preservation—A Systematic Review - Omid Fakheran; Kai R. Fischer; Patrick R. Schmidlin (Dentistry Journal, 2023)
Purpose: To systematically assess the current evidence regarding the adjunctive application of enamel matrix derivatives (EMDs) during alveolar ridge preservation (ARP) following tooth extraction. Methods: A comprehensive literature search was conducted in MEDLINE, Cochrane Library, PsycINFO, Web of Science, Google Scholar, and Scopus to identify relevant randomized controlled clinical trials (RCTs). The primary outcome parameters of this systematic review were histomorphometric and radiographic data; secondary outcomes were the feasibility of implant placement after ARP as well as patient-related outcomes such as postoperative discomfort. Results: The search identified 436 eligible articles published from 2011 to 2022, but only five were ultimately included for data extraction (146 patients). Given the substantial heterogeneity among the included studies, no meta-analysis could be performed. The authors’ qualitative analysis showed marginally improved outcomes regarding an increased percentage of new bone formation after tooth extraction and a reduction in postoperative discomfort. Conclusions: Given the potential value of EMDs in other fields of regenerative dentistry, more consideration should be given to EMDs as an adjunctive treatment option in ARP. However, more well-controlled randomized clinical trials are necessary to evaluate the exact potential and impacts of EMDs.